Republic of Serbia : Financial Sector Assessment Program Update; Technical Note on Deposit Insurance. (IMF Staff Country Reports; Country Report, 2010)
This Technical Note discusses key findings of the assessment of deposit insurance in Serbia. The deposit insurance scheme is managed by the deposit insurance agency (DIA), which has a multi-faceted mandate. Consequently, few DIA staff is actively involved in the core mandate of deposit insurance fund (DIF) management. DIA revenue sources are volatile, and DIF related revenues are used to subsidize non-DIF related activities. To improve transparency and ensure sustainability of the DIF, the legal framework should be amended to clarify the use of DIF resources and cap the use for operating costs.